MONOPOLI DAN PENIMBUNAN DALAM PANDANGAN EKONOMI ISLAM: IMPLIKASI TERHADAP KEADILAN (STUDI KASUS TOKO SEMBAKO AL MUNAWARAH) - Al Munawarah Al Munawarah; Arum Wijayanti (Ekonomi Syariah STAI Sangatta Kutai Timur, 2026)
This study examines monopoly and hoarding practices in Islamic economics and their implications for price fairness, using Al Munawarah Grocery Store as a case study. Monopoly and hoarding are economic practices that frequently occur in the distribution of basic necessities and negatively affect price stability and public welfare. The purpose of this study is to analyze these practices from the perspective of Islamic economics and evaluate their impact on small businesses. This study employs a descriptive qualitative research approach through observations, systematic and semi-structured interviews, and documentation. The collected data were then presented and analyzed to draw conclusions. The findings indicate that Al Munawarah Grocery Store does not engage in monopoly or hoarding practices; however, it is indirectly affected by such practices among large distributors. In Islamic economics, monopoly and hoarding are classified as forms of dzulm (injustice) and are contrary to the principle of al-maslahah al-'ammah (public interest). Therefore, effective market supervision and the implementation of justice-based principles are essential solutions for maintaining economic balance and ensuring price fairness.